Clinical and sociodemographic factors associated with preeclampsia in gestants of 16-25 years old attended in emergency in the ventanilla hospital of january-december 2016: Factores clínicos y sociodemográficos asociados a preclampsia en gestantes de 16-25 años atendidas en emergencia en el hospital de ventanilla de enero-diciembre 2016 - Llacuachaqui-Sánchez, Walter José (2018)
Objective: To determine the clinical and sociodemographic factors associated with pre-eclampsia in pregnant women aged 16-25 years treated at the Hospital de Ventanilla emergency in January-December 2016. Methods: An observational, analytical, cross-sectional study was conducted. We worked with 364 pregnant women from the hospital of Ventanilla. The following variables were measured: preclampsia (dependent), age, marital status, educational level, occupation, sexual partner, previous gestations, gestational age, BMI, gestational anemia, pregestational diabetes and gestational diabetes (independent). ORs were calculated with their respective 95% confidence intervals. A value of p less than 0.5 was considered significant. Results: The prevalence of preclampsia was 5.7%. the factors associated with preclampsia were: Marital status (OR: 0.16 (0.03-0.77)), Degree of instruction (OR: 0.31 (0.11-0.87)), Sex partner (OR: 0.36 (0.140.91)), Previous pregnancy ( OR: 2.99 (1.72-13.43)), BMI (OR: 4.47 (1.69-11.82)), Anemia (OR: 3.41 (1.22-9.52)), Pregestational DM (OR: 5.55 (1.43-21.94)). Conclusion: Preeclampsia was associated to civil status, degree of instruction, sexual partner, previous pregnancy, BMI, anemia and pregestational DM. Key words: Pre-eclampsia; Pregnancy; Emergency medical services. (source: MeSH NLM)   DOI: 10.25176/RFMH.v18.n2.1287